Aspartate transaminase/alanine transaminase (De Ritis ratio) predicts survival in major burn patients. Issue 4 (June 2022) - Wang, Baoli; Hu, Lunyang; Chen, Yukun; Zhu, Banghui; Kong, Weishi; Zhu, Zhe; Wang, Kangan; Yu, Qing; Zhang, Wei; Wu, Guosheng; Sun, Yu; Xia, Zhaofan
Highlights: The De Ritis ratio was identified as a new prognostic indicator for major burn patients, which can be conveniently obtained through blood examination. Regardless of whether the prediction was for 30-day or 90-day mortality, the accuracy remained high. Compared to serum albumin level, the De Ritis ratio was superior in assessing the prognosis of extensively burned patients. Abstract: Background: Although treatment of burn patients has significantly improved in recent decades, major burns remain fatal. Therefore, the evaluation of the death risk of the patients with extensive burns is very important. The ratio between the serum levels of aspartate transaminase and alanine transaminase (De Ritis ratio) was an independent predictor of poor outcomes in patients with acute ischemic stroke, cardiac surgery, non-metastatic renal cell carcinoma, and upper urinary tract urothelial carcinoma. Our aim was to determine whether the ratio between the serum levels of AST and ALT (De Ritis ratio) was useful to assess prognosis in extensively burned patients. Methods: We conducted a single-center cohort study at the Burns Department of Changhai Hospital. This retrospective observational analysis was performed based on the clinical data of major burn patients admitted between May 1, 2005 and April 30, 2018. Univariate and multivariate logistic regression analyses were performed on variables such as age, sex, total body surface area (TBSA), De Ritis ratio, and serum albumin level, which may affect mortality in major burn patients. We assessed their diagnostic value and found the cut-off value by receiver operative characteristic (ROC) curve analysis. We used the Kaplan–Meier curve to display the impact of the De Ritis ratio and serum albumin level on survival in burn patients. Results: A total of 351 patients with extensive burns were included in the study. The cohort predominantly consisted of males (74.64%), and most of the patients (78.35%) had been burned by a flame. Age, TBSA, inhalation, and the De Ritis ratio were found to be independent risk factors for the 30-days mortality of major burn patients, while age, TBSA, inhalation, and the De Ritis ratio were independent risk factors for 90-day mortality. Further, the De Ritis ratio was a better mortality predictor than serum albumin in severely burned patients, whose area under ROC for 30-day and 90-day mortality was 0.771 (95% confidence intervals [CI], 0.708–0.835) and 0.750 (95% CI, 0.683, 0.818). Conclusions: The De Ritis ratio was useful as a prognostic indicator for major burn patients, which can be conveniently obtained through blood examination. Regardless of whether the prediction was for 30-day or 90-day mortality, the accuracy remained high. Moreover, compared to serum albumin level, the De Ritis ratio was superior in assessing the prognosis of extensively burned patients.